2013
DOI: 10.1111/iej.12187
|View full text |Cite
|
Sign up to set email alerts
|

Apical extrusion of bacteria when using reciprocating single‐file and rotary multifile instrumentation systems

Abstract: All instrumentation systems extruded bacteria beyond the foramen. However, both reciprocating single-file systems extruded fewer bacteria apically than the conventional multifile rotary system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
99
3
11

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(113 citation statements)
references
References 23 publications
0
99
3
11
Order By: Relevance
“…Variability has been observed between different rotary systems in terms of debris extrusion (9). This is thought to be caused by differences in cross-section and cutting blade design of a particular system as well as taper, tip, configuration, concepts of use, flexibility, alloy, number of files, kinematics, and cutting efficacy (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variability has been observed between different rotary systems in terms of debris extrusion (9). This is thought to be caused by differences in cross-section and cutting blade design of a particular system as well as taper, tip, configuration, concepts of use, flexibility, alloy, number of files, kinematics, and cutting efficacy (10).…”
Section: Discussionmentioning
confidence: 99%
“…Variations in the root canal anatomy may influence the amount of apical extrusion of debris (1,10,24,32). Extrusion of debris in mandibular incisors has not been largely studied.…”
Section: Discussionmentioning
confidence: 99%
“…However, this fact does not represent a consensus in the recent specific literature. In a recent study, reciprocating single-file systems extruded fewer bacteria apically than a conventional multi-file rotary system (22). Moreover, other studies showed no differences between rotary and reciprocating movements regarding debris extrusion (23,24).…”
Section: Discussionmentioning
confidence: 94%
“…This can be explained by differences in terms of kinematic and number of file in systems. It has indicated that single-file reciprocating instruments with Gold wire metallurgy caused less bacterial extrusion (30) and debris than conventional multifile rotary systems. The results of the present study may be explained with this observation.…”
Section: Discussionmentioning
confidence: 99%